Therapeutic potential of ciclesonide inhalation for COVID-19 pneumonia: Report of three cases. Issue 6 (June 2020) - Iwabuchi, Keisuke; Yoshie, Koichiro; Kurakami, Yuichi; Takahashi, Kota; Kato, Yoshio; Morishima, Tsuneo
Abstract: No specific and effective anti-viral treatment has been approved for COVID-19 so far. Systemic corticosteroid has been sometimes administered to severe infectious diseases combined with the specific treatment. However, as lack of the specific anti-SARS-CoV-2 drug, systemic steroid treatment has not been recommended for COVID-19. We report here three cases of the COVID-19 pneumonia successfully treated with ciclesonide inhalation. Rationale of the treatment is to mitigate the local inflammation with inhaled steroid that stays in the lung and to inhibit proliferation of the virus by antiviral activity. Larger and further studies are warranted to confirm the result of these cases.